Tutoriale jako przykład materiału autentycznego stymulującego motywację w samodzielnym przyswajaniu leksyki obcojęzycznej - Targ, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
This article discusses the influence of tutorials on motivation to learn foreign lexis. The author quotes the definition of a tutorial and describes its characteristics. Moreover, the author presents research findings which aimed at verifying how frequently tutorials are used and learners' abilities to work with such foreign materials, as well as the evaluation of their motivational value.
Keywords: tutorial; materiały autentyczne; motywacja; samokształcenie; tutorial; authentic materials; motivation; self-learning